Fly Density and Identification Analysis and Control Efforts In Traditional Market Purwokerto - Agus Subagyo; Arif Widyanto; Aris Santjaka (Poltekkes Kemenkes Semarang, 2014)
The purpose of this study was to determine the density of flies, fly types, sanitary conditions, and the control efforts in Wage Market and Manis Market Purwokerto. This descriptive research only describes about those 4 points. Data obtained is then analyzed in tabular form by comparing the measurement results with existing standards. The result of the density of flies in Wage Market and Mains Market is 6 tails / grill block. It is categorized as the high density so there should be a protective system against the breeding places of flies. Moreover, there are no efforts to control flies at Wage Market and Manis Market. The conclusions of this study are in the Wage Market and Manis Market there are high densities of flies, so there should be a control for this phenomena. Species found are Musca Domestica, Sarcopaga sp and Phaenicia sp. Some suggestions of fly control efforts are by giving some covers to the common trash bins and waterproof trash bins, and to increase the intensity of transporting trash from TPS to TPA that previously 3 times to 4 times in the Wage Market and 2 times to 3 times in Manis Market.